Honorary blood donations in urban and rural areas in Poland - Dominik Olejniczak; Ewa Grochowska; Aleksandra Czerw; Grzegorz Juszczyk; Urszula Religioni; Aneta Duda-Zalewska; Anna Staniszewska; Marcin Mikos (Kazimierz Wielki University, 2015)
Olejniczak Dominik, Grochowska Ewa, Czerw Aleksandra, Juszczyk Grzegorz, Religioni Urszula, Duda-Zalewska Aneta, Staniszewska Anna, Mikos Marcin. Honorary blood donations in urban and rural areas in Poland. Journal of Education, Health and Sport. 2015;5(6):65-72. ISSN 2391-8306. DOI 10.5281/zenodo.18278 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A65-72 https://pbn.nauka.gov.pl/works/563208 http://dx.doi.org/10.5281/zenodo.18278 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2015. Revised 28.05.2015. Accepted: 04.06.2015.     Honorary blood donations in urban and rural areas in Poland   Dominik Olejniczak1, Ewa Grochowska1, Aleksandra Czerw1, Grzegorz Juszczyk1, Urszula Religioni1, Aneta Duda-Zalewska1, Anna Staniszewska2, Marcin Mikos3   1Department of Public Health, Medical University of Warsaw, Poland 2Department of Experimental and Clinical Pharmacology, Medical University of Warsaw, Poland 3Institute of Public Health, Jagiellonian University Medical College, Cracow, Poland, e-mail address of correspondence: ola_czerw@wp.pl   Abstract   Aim The main purpose of the study was to compare blood donation awareness among students  residing in urban and rural areas. Subject and methods The research tool was an anonymous, original questionnaire designed for the purpose of the study. The questionnaire was distributed among 439 people. In the first stage, authors selected randomly two fields of study at Medical University of Warsaw. Next, three years of study were randomly selected in these two chosen fields. Results Nearly 40% of the students admitted that they have donated blood or other compounds. There is statistically significant relation (p=0.0000, Fi=0.25) between blood donation and place of residence of respondents. Students living in cities more seldom showed they have donated blood or other compound. The most common reason that impels students to donate blood is the desire to help another human being. Conclusions The level of students' knowledge about blood donations issue is not good enough. It is recommended to introduce intensive information campaigns about the need of blood donation, for example in the form of social campaigns.   Key words: blood donations, donor, blood transfusion, health promotion.